Database Access Control in a Database Keyword Search Tool - Monteagudo Garcia, Grettel; Guillot Jiménez, Javier; Batista Neves Júnior, Angelo; Torres Izquierdo, Yenier; Lemos, Melissa; Casanova, Marco A.; Ferreira, Ana Cristina; Texeira da Silva, Flavia Pacheco (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2023: Anais do XXXVIII Simpósio Brasileiro de Bancos de Dados, 2023)
This paper addresses the access control problem in the context of database keyword search, when a user defines a query by a list of keywords, and not by SQL (or SPARQL) code. It describes the solutions implemented in DANKE, a database keyword search platform currently used in several industrial applications. DANKE offers two alternatives for managing access control: given a keyword query K and the user permissions P, either compile K into the same structured query and filter the results based on P, or compile K into different structured queries, depending on P. Likewise, DANKE has two alternatives for defining the user permissions: using the features of the database management system, or using an internal mechanism.